Potential of using web-based animated and interactive maps in teaching geography - Raman, Arumugam (DonEl Learning Inc, 2009)
Students at upper secondary school are experiencing difficulty with mastery of geographic skills such as identification and interpretation of geographical information and also map reading. This trend may occur due to the nature of geography discipline that requires creative and critical thinking.Web-based technologies may have the potential to transform the way geography education is delivered to secondary school students.It may enhance teaching and learning process in the classroom and attract students to geography as a discipline.The aim of this study is to find whether the students trained to read animated and interactive maps via web are able to perform better than students using printed static maps in problem solving and explaining symbols. Students in form four were tested on three aspects of geography: map reading, feature recognition and geographical concepts. Students were not randomly assigned to instruction but randomly assigned for post-test.Multivariate analysis of variance (MANOVA) indicated that students performing using animated maps outperformed students using computer delivered static maps.This study reveals that students using web-based animated and interactive maps exhibit stronger understanding of geographical concepts and improve their map-reading skill.